(untitled) (Journal of Educational Sciences, 2017)
The article is devoted to formation of professional competences of specialists-bachelors within distance learning on the basis of the competency model of a specialist, which is developed by KazUIR&WL, comprising 4 blocks of competences including subcompetences: intercultural and communicative competence, professionally-oriented competence, professionally-based competence, professionally-identifying competence. In the context of distance learning, the formation of these competences acquires a greater professionalism and leads to a better professional readiness of a specialist in the international labor market. Since 2016-2017 academic year the university has switched to a new version of Moodle 3.1. This version is completely different from the previous version of Moodle 2.1. The main improvement is the updated interface of the system. Version 3.1 of SDO Moodle, includes functionality of management of the system users skills. The main advantage of this is Competency-Based Education (CBE). About 50 e-courses on two specialties “Foreign language: two foreign languages” and “Translation studies” for introduction in DO have been developed. Key words: professional readiness of a specialist, intercultural and communicative competence, professionally-oriented competence, professionally-based competence, professionally-identifying competence, distance learning.